2013
DOI: 10.1021/je301076n
|View full text |Cite
|
Sign up to set email alerts
|

Dye Adsorption by Leather Waste: Mechanism Diffusion, Nature Studies, and Thermodynamic Data

Abstract: Tannery solid waste (leather) is a possible adsorbent of dye contaminants in wastewater. In this paper the nature and mechanisms of dyes adsorption by chromium-tanned leather waste (CTLW) are proposed and discussed on the basis of isotherms, adsorption kinetics, and thermodynamics of three dyes: Red 357, Black 210, and Yellow 194 in aqueous solutions. Langmuir, Brunauer–Emmett–Teller (BET) and Henry isotherm models were used to fit the adsorption equilibrium data, respectively. The kinetic data were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 36 publications
0
31
0
2
Order By: Relevance
“…The 10 discharge of industrial wastewater containing different dye 11 contaminants causes serious environmental problems. A variety 12 of methods such as adsorption, coagulation and flocculation, 13 oxidation, chemical precipitation, and so forth, have been reported 14 for waste water treatment [1][2][3][4][5][6][7]. Among these, adsorption is well 15 established and superior technique because of their low cost, the 16 simplicity of design and availability of adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The 10 discharge of industrial wastewater containing different dye 11 contaminants causes serious environmental problems. A variety 12 of methods such as adsorption, coagulation and flocculation, 13 oxidation, chemical precipitation, and so forth, have been reported 14 for waste water treatment [1][2][3][4][5][6][7]. Among these, adsorption is well 15 established and superior technique because of their low cost, the 16 simplicity of design and availability of adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…95 New effluent treatment techniques, such as adsorption of dyes from leather dyeing, have been shown to be successful. 68 As for the effluents from the tanning stage, the recycling of these is still not practiced comprehensively in the industry and there are uncertainties about the actual necessary dosage of chemical reagents responsible for the precipitation of chromium. The precipitation for chromium removal from tanning wastewater enables the reuse of the metal when it is redissolved to be used again in the process.…”
Section: Resultsmentioning
confidence: 99%
“…[66][67][68] Adsorption is a transfer process of one or more constituents (adsorbates) of a fluid phase (adsorptive) to the surface of a solid phase (adsorbent). In the adsorption process, molecules present in the fluid phase are attracted to the interfacial zone due to the existence of uncompensated attractive forces at the surface of the adsorbent.…”
Section: Other Treatment Techniques For Chromium Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the high values of R 2 presented in Table 2, it can be seen that the Langmuir (equation (8)) and BET models (equation (9)) were able to explain the equilibrium adsorption of Acid Red 357 and Acid Black 210, respectively. Table 2 shows also the thermodynamic parameters, which were estimated by the Van't Hoff's plot (Piccin et al, 2013). The negative DG values indicated that the dyes adsorption onto TSW was a spontaneous and favorable process.…”
Section: Equilibrium Isothermsmentioning
confidence: 99%